2002
DOI: 10.1385/ir:25:3:261
|View full text |Cite
|
Sign up to set email alerts
|

The Interface Between Tapasin and MHC Class I Identification of Amino Acid Residues in Both Proteins That Influence Their Interaction

Abstract: Prior to the binding of antigenic peptide, a complex of chaperone proteins associates with the Major Histocompatibility Complex (MHC) class I heavy chain/beta2m heterodimer. Although each domain of the MHC class I heavy chain contains amino acid residues that influence chaperone binding, there are several pieces of evidence that point to an interaction between the MHC class I alpha/2/alpha3 domains and tapasin. In regard to the site on tapasin involved in the tapasin/MHC interface, we have found that a particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 42 publications
2
14
0
Order By: Relevance
“…Thus, it is rather unlikely that TM segments of MHC I play any role in the TMLZ-mediated complex formation between TAP and TPN. This is in line with the hypothesis that TPN and MHC I interact with each other via their ER luminal domains (70). The TMLZs of TM1 and TM2 are present in both TAP chains at corresponding sequence positions.…”
Section: Discussionsupporting
confidence: 90%
“…Thus, it is rather unlikely that TM segments of MHC I play any role in the TMLZ-mediated complex formation between TAP and TPN. This is in line with the hypothesis that TPN and MHC I interact with each other via their ER luminal domains (70). The TMLZs of TM1 and TM2 are present in both TAP chains at corresponding sequence positions.…”
Section: Discussionsupporting
confidence: 90%
“…To establish these contacts, the C-terminal domain of Tsn has to rotate compared with its initial orientation in the X-ray crystal structure. The C-terminal Tsn residues observed in our MD simulations have previously been suggested to be involved in the interaction and have been shown to influence assembly and surface expression of MHC I molecules (52)(53)(54)(55).…”
Section: Mechanism Of Differential Bindingmentioning
confidence: 60%
“…2 and 4), this tapasin region probably contacts L d . Previous studies found evidence for interaction sites on both the MHC class I ␣2 and ␣3 domains for tapasin (7,38,54,55). Given that aa 334 -342 of tapasin are modeled to be at a membrane-distal position in the three-dimensional structure of the tapasin Ig-like domain (Fig.…”
Section: Discussionmentioning
confidence: 99%